Burden of Hyperglycemia in Patients Receiving Corticosteroids for Severe COVID-19 - Kirk B. Fetters, M.D; Stephen P. Judge, MD; Eric S. Daar, MD; Timothy J. Hatlen, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2022)
Although corticosteroid therapy is the standard of care for all patients hospitalized with severe coronavirus disease 2019 (COVID-19), the studies demonstrating the mortality–benefit ratio of corticosteroids were limited to fully evaluate their adverse effects. To determine the severity of corticosteroid-induced hyperglycemia in patients with and without diabetes mellitus, we retrospectively collected data from the medical records of patients hospitalized with COVID-19 before and after corticosteroids were the standard of care. Corticosteroid-induced hyperglycemia was more severe in patients hospitalized with COVID-19 with diabetes than those without diabetes. Additionally, patients with diabetes required higher doses of correctional insulin per day when on corticosteroid therapy, suggesting that intensive point-of-care glucose monitoring could be limited in patients without diabetes mellitus and support cautionary use of corticosteroids in patients with COVID-19 discharged with supplemental oxygen.